PERBANDINGAN MEKANISME PENINDAKAN ATAS PELANGGARAN LALU LINTAS TILANG MANUAL DENGAN PELANGGARAN LALU LINTAS SISTEM TILANG ELEKTRONIK (SYSTEM ELECTRONIC TRAFFIC LAW ENFORCEMENT) DI WILAYAH HUKUM POLDA SUMATERA BARAT - Putri Nandi Hayati; Lola Yustrisia; Riki Zulfiko (Ensiklopedia of Journal, 2023)
Abstract: The development of road transport infrastructure has an important role in supporting economic activities, but on the other hand it creates various problems related to violations of traffic laws, accidents, irregularity of road users and congestion. To prevent this, it is necessary for law enforcement officials who have the authority and responsibility for security and order in the State to be the Indonesian National Police (hereinafter referred to as the POLRI) as a tool of state law enforcement, protector, protector and public servant as stated in their main duties, namely in Article 13 Law Number 2 of 2022 concerning the Indonesian National Police. With the development of technology, the National Police Chief General; Listyo Sigit Prabowo formed a system related to ticketing. Electronic Traffic Law Enforcement (ETLE) is a fine system that uses an information technology basis with the main device being a camera. Indonesia finally did the same thing through the issuance of the Chief of Police's Telegram (TR) Number: ST/2264/X/HUM.3.4.5./2022 dated 18 October 2022. The type of research used in this writing is Empirise Research. Based on the results of this study: to implement electronic ticketing effectively due to reducing interaction between drivers and police officers and also to increase public awareness, especially drivers, to comply with traffic regulations.  Keywords: Comparison, Tickets Manual, Electronic Tickets .